Potential effects of broccoli extract (Brassica oleracea var. italica) on collagen fiber density in the wound healing process - Hakim, Rachmi Fanani; Fakhrurrazi, Fakhrurrazi; Andini, Yulia Rizky (Universitas Padjadjaran, 2023)
ABSTRACTIntroduction: Wound healing is a protective function of the body that focuses on quick recovery, where the regeneration process in a hostile environment takes more time. In particular, the oral cavity is a remarkable environment in which wound healing occurs in warm oral fluid that contains millions of microorganisms. Collagen plays an important role in all phases of wound healing, which provides integrity and strength to tissues, and it is very important especially in the proliferation and remodeling phases. One of the materials that have potential related to collagen is broccoli (Brassica oleracea var. italica). Broccoli has the potential to regulate collagen; therefore, it could be an alternative to answer the problem related to anti-inflammatory, antioxidant, and antimicrobial effects. The aim of this research is to analyze the potential effects of broccoli extract on collagen image in wounds. Methods: This research used 18 male Wistar rats with wounds created by incisions on each of the rats’ backs. These rats are divided into two groups, the control group, which received no treatment, and the treatment group, which was treated by applying the broccoli extract topically twice a day. Wound tissues on each group were observed microscopically on the 3rd, 7th, and 14th day. The density of collagen fibers was measured based on the calculation of semiquantitative score. Results: The result showed that wound healing in the treatment group looked better compared to that in the control group, with an increase in collagen score in the treatment group. The result of the statistical test Man-Whitney with confidence level 95% (p < 0,05) with observation on 3rd, 7th, and 14th days sequentially was p = 0.100, p = 0,100, p = 0,700. Conclusion: Broccoli extract which is applied topically, tends to have more benefits in terms of wound healing process, even though there is no significant difference found on the statistical tests.